Robust aerodynamic design of nacelles for future civil aero-engines - Schreiner, B. Deneys J.; Tejero, Fernando; MacManus, David G.; Sheaf, Christopher T. (American Society of Mechanical Engineers (ASME), 2021)
As the growth of aviation continues it is necessary to minimise the impact on the environment, through reducing NOx emissions, fuel-burn and noise. In order to achieve these goals, the next generation of Ultra-High Bypass Ratio engines are expected to increase propulsive efficiency through operating at reduced specific thrust. Consequently, there is an expected increase in fan diameter and the associated potential penalties of nacelle drag and weight. In order to ensure that these penalties do not negate the benefits obtained from the new engine cycles, it is envisaged that future civil aero-engines will be mounted in compact nacelles. While nacelle design has traditionally been tackled by multi-objective optimisation at different flight conditions within the cruise segment, it is anticipated that compact configurations will present larger sensitivity to off-design conditions. Therefore, a design method that considers the different operating conditions that are met within the full flight envelope is required for the new nacelle design challenge. The method is employed to carry out multi-point multi-objective optimisation of axisymmetric aero-lines at different transonic and subsonic operating conditions. It considers mid-cruise conditions, end-of-cruise conditions, the sensitivity to changes in flight Mach number, windmilling conditions with a cruise engine-out case and an engine-out diversion scenario. Optimisation routines were conducted for a conventional nacelle and a future aero-engine architecture, upon which the aerodynamic trade-offs between the different flight conditions are discussed. Subsequently, the tool has been employed to identify the viable nacelle design space for future compact civil aero-engines for a range of nacelle lengths.